2021
DOI: 10.1007/s11012-020-01274-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the motorcar body side deformation process during front-to-side vehicle collision and the emergence of a hazard to car occupants

Abstract: The kinematics of the process of deformation of the motorcar body side in the culminating phase of a front-to-side vehicle collision has been examined as a possible basis for analyzing and modeling the process of emergence of a hazard to car occupants during a road accident. The course of such accidents has a complex nature and their models are necessarily based on the approximation of non-linear elastoplastic characteristics of impact processes, especially during the transition from the compression phase to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…The acceleration designated as part of the conducted testing can be used to assess the driver's behaviour and in accident cause analysis [17,18]. The acceleration values presented are limit values for the tested vehicle type.…”
Section: Discussionmentioning
confidence: 99%
“…The acceleration designated as part of the conducted testing can be used to assess the driver's behaviour and in accident cause analysis [17,18]. The acceleration values presented are limit values for the tested vehicle type.…”
Section: Discussionmentioning
confidence: 99%
“…A model of the front-to-side vehicle collision was prepared in the MATLAB program and has been preliminarily presented by the authors in [37] and in Fig. 7.…”
Section: Model Of the Front-to-side Vehicles' Collisionmentioning
confidence: 99%
“…The procedure of validation of the front-to-side vehicle collision model has been presented by the authors in [37]. The parametrisation and validation of the model was based on results of front-to-side vehicle crash tests (cf.…”
Section: Validation and Parametrisation Of The Modelmentioning
confidence: 99%
“…When considering passenger comfort affected by the vehicle's operation and exploitation, it is necessary to specify such parameters as the vehicle's technical condition, seating ergonomics, noise and temperature in the passenger space. Examples of studies can be found in papers [15][16][17][18]. Lateral acceleration is one of the parameters used to assess a driver's behaviour and the comfort of urban bus passengers.…”
Section: Introductionmentioning
confidence: 99%